PENGARUH PENAMBAHAN STARTER TERHADAP KARAKTERISTIK PROSES PENGOMPOSAN DAN KUALITAS KOMPOS LIMBAH PABRIK AGAR - L. Sahwan, Firman (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Solid waste from Ã¢â‚¬Å“agar-agarÃ¢â‚¬Â (gelation made of seaweed) factory in huge amount and hasÃ‚Â potency to pollute the environment if it is not well managed, obviously has opportunityÃ‚Â to be used as compost. The purpose of this research is to find out the characteristic ofÃ‚Â composting process of agar-agar factoryÃ¢â‚¬â„¢s waste, and the quality of its compost product,based on 2 ( two ) treatments i.e. with and without the use chicken manure starter. InÃ‚Â general, result of the research showing that there is no significant different betweenÃ‚Â using chicken manure starter and not using chiken manure starter, with understandingÃ‚Â that both composting process can be done in aerobic condition (normal) with compostÃ‚Â quality according to mature compost criteria. However, specifically the rate of wasteÃ‚Â decomposition (composting process) of using chicken manure starter looks faster inÃ‚Â initial period of decomposition.Key words : compost, Ã¢â‚¬Å“agar-agarÃ¢â‚¬Â factory waste, chiken manure starter.